La Inobservancia de la Bancarización y sus efectos Tributarios en los principales contribuyentes del distrito de Tarapoto. Periodo 2012 - 2013 - Santa Cruz Valderrama, Ruth Nelly (2015)
This research aims to analyze the failure of banking to determine the tax effects in Major Contributors Tarapoto district. Period 2012 - 2013 and to establish proper procedures for its determination, so as to be optimal management facilitators in the main contributors Tarapoto district. The research method used is basic, because it is given to know the tax effects of not complying with the provisions of this law of banking ; and descriptive as disclosed facts and most important features of the subject matter , this determines the tax effects and economic result as well as the causes of product failure in business banking as major contributors district of Tarapoto. For the development of this work has applied the process and scientific procedures and methodologies, techniques, instruments established school rules Accounting from the National University of San Martin. At the conclusion of the investigation it was determined that the tax effects trucking is the lack of deductible expenses and the tax credit, impacting the accounting and economics; the failure of banking has a main factor the lack of tax culture by Top contributors Tarapoto District; tax effects that come with failure not allow deducting costs and expenses affecting the determination of income Tax and Tax Credit. The degree of banking in Top Contributors is high but there is still a small gap that not even 5%; for it was determined that the solution is to conduct its operations with non- performing correctly. The correct application of the banking permitted to obtain deductible expenses and may give right to use the tax credit which in modern business management impact on optimizing profits of the major contributors Tarapoto district